Analisis Variasi Desain Rangka Sepeda Motor Listrik Terhadap Kekuatan Rangka dengan Ansys Workbench - Mulyaningsih, Nani; Ramadhani, Wahyuchandra; Hastuti, Sri (Fakultas Teknik UMSU, 2023)
Designing a fuel-based electric motorcycle frame needs to be modified to be able to place electrical components. Design and simulation of frame design variations are needed to obtain optimal frame strength by having the lowest stress, lowest deformation, and highest safety factor. The research objective is to obtain a frame design with optimal frame strength. The research method uses a comparative method in the form of three frame design variations simulated by Ansys Workbench. The frame simulation uses two types of loads, namely normal loads (146.2 kg) and heavy loads (316.2 kg). The simulation material uses AISI 4130 material. The selected and optimal frame design is the frame with the lowest maximum von Mises stress value and not more than the yield stress, the lowest maximum total deformation, and the highest minimum safety factor and 2.5. From the research results, it was found that design 2 was the design with the best strength compared to design 1 and design 3. Simulation with normal load (146.2 kg) obtained a maximum von Mises stress of 50.38 MPa, maximum total deformation of 0.036 mm, minimum safety factor of 8.237. While the heavy load simulation (316.2 kg) obtained a maximum von Mises stress of 144.64 MPa, a maximum total deformation of 0.863 mm, a minimum safety factor of 2.869.